2023
DOI: 10.1021/acs.jpcc.3c01998
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Dopants in Plasmonic Nanocatalysts

Abstract: Bimetallic nanostructures combining plasmonic and catalytic metals are promising for tailoring and enhancing plasmonic hot-carrier generation utilized in plasmonic catalysis. In this work, we study the plasmonic hot-carrier generation in noble metal nanoparticles (Ag, Au, and Cu) with single-atom dopants (Ag, Au, Cu, Pd, and Pt) with first-principles time-dependent density functional theory calculations. Our results show that the local hot-carrier generation at the dopant atom is greatly altered by the dopant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Moreover, recent theoretical studies propose that HC generation at the dopant atom can be modulated with appropriate dopants. 70 The initial phase of our study involves a comprehensive analysis of the electronic structure of the studied systems. Electronic structure analysis is conducted by examining the PDOS, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent theoretical studies propose that HC generation at the dopant atom can be modulated with appropriate dopants. 70 The initial phase of our study involves a comprehensive analysis of the electronic structure of the studied systems. Electronic structure analysis is conducted by examining the PDOS, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…55 The characteristics of prototypical plasmonic nanoparticles with single-atom dopants were investigated. 70 It showed that while the overall plasmonic response of the nanoparticle is largely unaffected, the dopant element has a significant impact on the local HC generation at the atom. While most theoretical and computational studies have primarily focused on analyzing single-component ligand-free metallic nanoparticles, the investigation of how HCs are generated and distributed within multi-component ligated metallic nanoparticles remains a relatively unexplored area of research.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant progress has been made in theoretical investigations employing real-time time-dependent density functional theory (rt-TDDFT) 50–57 simulations to gain insights into the generation and distribution of HCs. 30,33,58,59 In a previous rt-TDDFT investigation, 60 H 2 dissociation on linear Ag chains (up to n = 12) revealed the delocalization of charge density over time on both H 2 and Ag chains. Additionally, in another rt-TDDFT study, 61 using Ag and Au nanoparticles with 19, 55, and 225 atoms, dissociation of O 2 and N 2 at variable heights above the nanoparticles was observed.…”
Section: Introductionmentioning
confidence: 84%
“…However, recently there has been increased interest in multicomponent NPs, such as antenna-reactor, 29−31 core−shell, 32 or singleatom alloys. 29,33 This interest is motivated by the fact that typical plasmonic metals (Ag, Au, or Cu) have the right optical properties but are poor traditional catalysts. In fact, using NPs with a plasmonic core and a catalytic surface alloy, several groups 29,30,32 have achieved better photocatalytic rates than with single-component systems.…”
mentioning
confidence: 99%
“…The collective electronic excitation is called a localized surface plasmon (LSP) and is particularly strong in noble metal NPs, manifesting as a large optical absorption cross section at visible frequencies. , Prototypical plasmonic metals such as Ag, , Au, ,, or Cu , are used due to their outstanding optical properties. However, recently there has been increased interest in multicomponent NPs, such as antenna-reactor, core–shell, or single-atom alloys. , This interest is motivated by the fact that typical plasmonic metals (Ag, Au, or Cu) have the right optical properties but are poor traditional catalysts. In fact, using NPs with a plasmonic core and a catalytic surface alloy, several groups ,, have achieved better photocatalytic rates than with single-component systems.…”
mentioning
confidence: 99%